Influence of molybdenum on corrosion and mechanical properties of carbon steel joint welds - Makarenko, Valerii; Vynnykov, Yuriy; Manhura, Andrii (Academic journal Industrial Machine Building Civil Engineering, 2019)
The results of experimental studies of the molybdenum impurity influence on corrosion and mechanical properties of carbonsteel (Grade 20) joint welds are presented in the article. In particular, it has been found that the highest and stable values ofthe impact strength and resistance properties of cracks (К1s and δs), as well as the resistance to sulfide corrosion cracking ofthe metal of tubular steel joints, are achieved at a concentration of molybdenum in it from 0,2 to 0,4%, which is realized byputting a molybdenum powder in the electrode coating in the amount of 0,5-1,0%. On the basis of the obtained results an optimalchemical composition of the weld metal was determined which is characterized by a fine-grained structure with a smallamount of non-metallic impurities of globular shape. Optimal content of the doping micro-additive - molybdenum should beselected, based on both the influence of molybdenum on the size of structural components, but, most importantly, on its effecton the corrosion and mechanical properties of metal joint weld.
Keywords: welding; corrosion; crack resistance; strength; sulfide; hydrogen